Akut lenfoblastik lösemili çocuk hastaların beyin omurilik sıvısı oksidan/antioksidan seviyeleri - KOÇ, AHMET (My University, 2014)
Objective: To assess the effect of leukemia therapy on the cerebrospinal fluid (CSF) antioxidant and oxidant status in children with acute lymphoblastic leukemia (ALL). Material and Method: Twenty-four consecutive children (15 boys and 9 girls) newly diagnosed with ALL were enrolled in the study. CSF concentrations of ceruloplasmin ferroxidase activity, total thiol group, lipid hydroperoxide (LOOH) and total oxidant status (TOS) were evaluated at diagnosis, remission induction, consolidation, continuation, and the end of the continuation. Nineteen children (10 boys and 9 girls) were enrolled as a reference group. Results: The study group at diagnosis had significant higher mean ferroxidase activity (50.2 ± 10.4 U/L and 30.3 ± 7.9 U/L), total thiol (0.34 ± 0.02 µmol/Land 0.18 ± 0.01 µmol/L), LOOH (6.5 ± 1.9 µmol/Land 5.3 ± 0.8 µmol/L), and TOS (9.3 ± 4.3 µmol H O equiv./L and 6 ± 1.5 H O equiv./L) levels compared with the 2 2 2 2 references, respectively (P < 0.05).. Ferroxidase activity remained elevated during the entire treatment course. Total thiol levels stayed elevated from diagnosis to week 80 of ALL treatment and significantly decreased thereafter. LOOH levels were progressively increased to week 80 of the treatment course. TOS levels were progressively decreased two times at continuation week 7 and end of the treatment. Conclusions: Our data indicate that CSF oxidative stress and antioxidants are higher at diagnosis, significant changes to be during therapy, and is already high at the end of therapy in children with ALL. Key Words: Acute lymphoblastic leukemia, antioxidants, cerebrospinal fluid, oxidants, oxidative stress

Amaç:Akut lenfoblastik lösemili çocuk hastalarda tedavinin beyin omurilik sıvısında (BOS) antioxidant ve oksidan seviyelerini araştırmak. Materyal ve Metod: 24 (15 erkek 9 kız) yeni tanı almış hastaların tanı anında, remisyon indüksiyon, güçlendirme, idame ve tedavi sonunda BOS seruloplazmin ferroksidaz aktivitesi, total tiyol, lipid hidroperoksit (LOOH), ve total oksidant seviyeleri (TOS) çalışıldı. Çalışmaya 19 çocuk (10 erkek 9 kız) (kontrol) olarak alındı. Bulgular: İlk tanıda ALL grubunda kontrol grubuna göre sırasıyla, ortalama ferrokisdaz aktivitesi (50.2 ± 10.4 U/Lve 30.3 ± 7.9 U/L), total tiyol (0.34 ± 0.02 µmol/Lve 0.18 ± 0.01 µmol/L), LOOH (6.5 ± 1.9 µmol/L ve 5.3 ± 0.8 µmol/L), ve TOS (9.3 ± 4.3 µmol H O equiv./L ve 6 ± 1.5 H O equiv./L) bulundu (P < 0.05). 2 2 2 2 Ferroksidaz aktivitesi tüm tedavi süresince yüksek seyrettiği, total tiyol seviyesinin ise tedavinin ilk 80 haftasında yüksek kaldığı daha sonra azlamaya başladığı, total oxidant seviyenin ise idamenin 7 haftası ile 120 haftasında düşüşler gösterdiği saptandı. Sonuç: ALL'li çocuk hastaların BOS oksidan stresi ve antioksidanları yüksek seviyededir ve tedavi süresince bu yükseklik devam etmektedir. Anahtar kelimeler:Akut lenfoblastik lösemi, antioksidanlar, beyin omurilik sıvısı, oksidanlar, oksidan stress
Cerebrospinal fluid oxidant/antioksidant status in children with acute lymphoblastic leukemia
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Pediatric Hematology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Tıp Genel & Dahili; Pediatri; Clinical Medicine (Med); Clinical Medicine; Medicine General & Internal; Pediatrics; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Pediatri, Perinatoloji ve Çocuk Sağlığı; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pediatrics, Perinatology and Child Health; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Akut lenfoblastik lösemi; antioksidanlar; beyin omurilik sıvısı; oksidanlar; oksidan stress; Acute lymphoblastic leukemia; antioxidants; cerebrospinal fluid; oxidants; oxidative stress